(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article examines the difficulty of being Human from philosophical, psychological, and existential perspectives. The main focus is on the inner conflict experienced by individuals who, in striving for harmony and inner peace, are inevitably confronted with their own weaknesses, illusions, and limitations. The article analyzes ideas from ancient philosophers (Plato and Aristotle), as well as existentialist thinkers such as Jean-Paul Sartre, who argues that man is freedom compelled to struggle against the constraints of his own nature. The psychological dimension is explored through Carl Jung’s concept of projection and defense mechanisms, such as hatred toward others, which help a person avoid facing their own flaws. The article concludes that genuine Human existence is possible only through the recognition and acceptance of one’s inner complexity, the acknowledgment of darker aspects of the self, and the ability to be sincere and harmonious in relationships with others. Being Human requires continuous self-development and self-knowledge, which are the keys to a meaningful and internally integrated life.